What lies behind the large genome of Colletotrichum lindemuthianum - da Silva, Leandro Lopes; Correia, Hilberty Lucas Nunes; Gonçalves, Osiel Silva; Vidigal, Pedro Marcus Pereira; Rosa, Rafael Oliveira; Santana, Mateus Ferreira; de Queiroz, Marisa Vieira (Frontiers in Fungal Biology, 2024)
Colletotrichum lindemuthianum is the etiological agent of anthracnose disease in common bean (Phaseolus vulgaris L.), noted for its ability to cause serious damage and significant pathogenic variability. This study reveals the features of the high-quality genome of C. lindemuthianum. Analysis showed improvements over the first assembly, with the refined genome having 119 scaffolds, ten times fewer than the first, and a 19% increase in gene number. The effector candidates increased by nearly 1.5 times. More than 40% of the amino acid sequences with homologs in the Pathogen-Host Interactions (PHI-base) database are linked to pathogenicity. Of 18 putative proteins identified as Chitinase-like Protein, six have a mutation in the enzyme catalytic motif, and three showed gene expression in the biotrophic phase, indicating they can act as effectors. Comparative genomic analyses with 30 other fungal species revealed that C. lindemuthianum is among the top three fungi encoding transport proteins. Seven Necrosis and Ethylene-Inducing Peptide 1 (Nep1)-Like Proteins (NLPs) are present in the C. lindemuthianum genome, but none had complete identity with the GHRHDWE conserved motif of NLPs; two were grouped with proteins that induce necrosis and may retain the capability to induce host necrosis. Colletotrichum species show a high number of secondary metabolite (SM) clusters, with C. lindemuthianum having 47 SM clusters. Approximately 60% of the C. lindemuthianum genome is composed of repetitive elements, a significantly higher proportion than in other fungi. These differences in transposable element (TE) numbers may explain why C. lindemuthianum has one of the largest genomes among the fungi analyzed. A significant portion of its genome comprises retroelements, particularly the Ty1/Copia superfamily, which accounts for 22% of the genome and represents 40% of the repetitive elements. The genomic profile features a remarkably high RIP-affected genomic proportion of 54.77%, indicating substantial RIP activity within this species. This high-quality genome of C. lindemuthianum, a significant pathogen in common bean cultivation, will support future research into this pathosystem, fostering a deeper understanding of the interaction between the fungus and its host.